1998
DOI: 10.1074/jbc.273.1.309
|View full text |Cite
|
Sign up to set email alerts
|

RANTES and MIP-1α Activate Stats in T Cells

Abstract: RANTES1 (regulated on activation, normal T cell expressed and secreted) and MIP (macrophage inflammatory protein)-1␣ are potent chemoattractant cytokines (chemokines) for T cells (1-3). Accumulating evidence suggests that these CC or ␤-chemokines function as regulators of inflammatory and immunoregulatory processes (4 -15). Chemokines mediate their shared and different biologic effects through common receptors. Eight receptor cDNAs specific for the CC chemokines have been cloned to date, whose nine gene produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
103
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 44 publications
7
103
0
2
Order By: Relevance
“…In the context of chemokine-CCR5 interactions in T cells, these data infer that chemokine involvement in Stat activation will influence T cell activation mediated, in part, by cross-talk with the activated TCR. We have shown that CCL5 induces the expression of a putative Stat inducible gene, c-fos, in T cells [51]. The induction of c-fos gene expression correlated with the expression of CCR5.…”
Section: The Jak-stat Connectionmentioning
confidence: 82%
See 1 more Smart Citation
“…In the context of chemokine-CCR5 interactions in T cells, these data infer that chemokine involvement in Stat activation will influence T cell activation mediated, in part, by cross-talk with the activated TCR. We have shown that CCL5 induces the expression of a putative Stat inducible gene, c-fos, in T cells [51]. The induction of c-fos gene expression correlated with the expression of CCR5.…”
Section: The Jak-stat Connectionmentioning
confidence: 82%
“…It is now clear that ligand-induced chemokine receptor activation can also invoke Jak-Stat signaling, perhaps by a mechanism that requires receptor homodimerization and heterodimerization [39][40][41]47,49,50]. Nuclear extracts from Molt-4 and Jurkat T cells treated with CCL3 or CCL5 contained tyrosine phosphorylated Stat1:Stat1 and Stat1:Stat3 dimers that exhibited DNA-binding activity [51]. This activation was dependent on CCR5 gene expression.…”
Section: The Jak-stat Connectionmentioning
confidence: 99%
“…Although SDF-1-mediated activation of other members of the Jak/STAT family has also been described (17)(18)(19), we focused our work on the Jak2/STAT3 pathway because of its major role in GPCR signal transduction (18,(35)(36)(37) and survival signals (57). GPCRs contain four cytoplasmic domains, three loops (ICL1-3) and a C terminus part, that are potentially able to recruit signaling molecules leading to activation of a wide variety of cellular responses after ligand binding.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the Jak2/STAT3 pathway was described in several chemokine receptors such as CCR2b, CXCR4, CCR5, and platelet-activating factor receptor (PAFR) (18,(35)(36)(37) and Jak2 is required for SDF-1␣-induced activation of PI 3-kinase, tyrosine phosphorylation of multiple focal adhesion proteins and chemotaxis of hematopoietic progenitor cells (19). Other GPCRs such as luteinizing hormone, angiotensin II, PAR-1, and serotonin 5-HT 2A receptors also activate Jak2 after ligand binding (38 -42) underlying the role of Jak2 in GPCR signaling.…”
mentioning
confidence: 99%
“…A likely explanation would be that increased STAT-1 expression is a consequence of increased cytokine activity in the synovium. STAT-1 can be activated by a number of cytokines, including the type I and type II IFNs, interleukin-6 (IL-6), IL-9, IL-11, oncostatin M, and leukemia inhibitory factor, and by the chemokines RANTES and macrophage inflammatory protein 1␣ (43,44). Although the prototype STAT-1-inducing cytokine IFN␥ is barely detectable in the rheumatoid synovium, low doses of IFN␥ are able to sensitize the STAT-1 activation pathway, which has been shown to yield increased STAT-1 activity upon subsequent activation (40).…”
mentioning
confidence: 99%